TELAAH TERHADAP PENERAPAN PANDUAN RANCANG KOTA KAWASAN CIKINI PADA SUB KAWASAN 3 DAN 4 - Gandha , Maria Veronica; Enrico , Jeremiah; Meidana , Jessica; Tanesa , Wenni; Patricia, Mischa; Lukardi , Kelvin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The change in the status of the National Capital from Jakarta to East Kalimantan has had an impact on the arrangement of urban spaces in Jakarta. The city of Jakarta is planned to become a trade and services city. Flood management, spatial planning, and traffic jams are the 3 main things that the Acting Governor of DKI Jakarta concentrates on. Changes and development of cities have been thought about by creating urban spatial planning or what is often called the Urban Design Guideline (UDGL) or City Design Guide (PRK). The city government implies that every 5 years, this City Design Guide must be re-evaluated by looking at developments and changes that occur. This PKM tries to contribute by participating in evaluating the realization of the City DesignGuide in Jakarta. The focus of the PRK observations taken is the Cikini RegionPRK which has been stipulated in Gubernatorial Regulation No. 98 of 2020. The development of the region's vision as a center for trade and services, as well as a city-scale historical cultural tourism center integrated with mass public transportation, needs to be seen. The Cikini Region PRK evaluation is divided into 3 PKM activities which focus on sub-regions 1 and 2; 3 and 4; 5 and 6. This PKM will focus on sub-regions 4. The method used is a descriptive-comparative analysis by comparing the government's plans in the RPK content with real conditions in the field. Data were collected using literature review and survey methods and then continued with comparative analysis methods, evaluating the truth of what happened so that later conclusions could be drawn. It is hoped that this PKM can become a pilot project with partners in producing an evaluation book as input for the next Cikini Region PRK